Withdrawal of U.S. Military Engagement and The Erosion of Liberal Democratization: An Afghan Perspective - Subrat K. Ratha (Journal of Government and Political Issues, 2022)
The recent humanitarian catastrophe in Afghanistan denotes the failure of US-led liberal democratization in authoritarian and non-democratic countries, especially in the Muslim world. Having been witnessed a long-term war in a foreign land, after a detailed deliberation in the Doha agreement, the U.S. military stand-up has been overthrown with the rise of the Taliban. It can be viewed as a failed policy of the U.S. government since the emergence of the "War on Terror" to improve the stability in Afghanistan. Instead of allowing democratic reforms and good governance, the U.S. fulfilled its false desire to dismantle terrorism and religious fundamentalism. Ultimately, the U.S. completely degraded its moral strength to universalize democratic values and representative government. After bloody decades, all the U.S. military forces returned to their motherland with a bare hand but left an uncertain future for Afghan people that had to be resolved through consensus.